Intra-locked G-quadruplex structures formed by irregular DNA G-rich motifs - Maity, Arijit (2020)
G-rich DNA sequences with tracts of three or more continuous guanines (G≥3) are known to have high propensity to adopt stable G-quadruplex (G4) structures. Bioinformatic analyses suggest high prevalence of G-rich sequences with short G-tracts (G≤2) in the human genome. However, due to limited structural studies, the folding principles of such sequences remain largely unexplored and hence poorly understood. Here, we present the solution NMR structure of a sequence named AT26 consisting of irregularly spaced G2 tracts and two isolated single guanines. The structure is a four-layered G4 featuring two bi-layered blocks, locked between themselves in an unprecedented fashion making it a stable scaffold. In addition to edgewise and propeller-type loops, AT26 also harbors two V-shaped loops: a 2-nt V-shaped loop spanning two G-tetrad layers and a 0-nt V-shaped loop spanning three G-tetrad layers, which are named as VS- and VR-loop respectively, based on their distinct structural features. The intra-lock motif can be a basis for extending the G-tetrad core and a very stable intra-locked G4 can be formed by a sequence with G-tracts of various lengths including several G2 tracts. Findings from this study will aid in understanding the folding of G4 topologies from sequences containing irregularly spaced multiple short G-tracts.